Tourism in the construction of the idea of World Heritage (Unesco, 1960-1980) - Serpa Steinke, Valéria Fernanda (2023)
This article has as its central theme the construction of the idea of world heritage and its interfaces with tourism within Unesco, in the years 1960 to 1980. During the discussions on the construction of the Unesco’s Convention Concerning the Protection ofthe World Cultural and Natural Heritage (1972) in what terms was the approximation between (world) heritage and tourism being thought? In this sense, locating, understanding and problematizing how this rearrangement took place within Unesco is the main objective of this work, which is divided into two parts. In the first one, the emergence of tourism in the debate on world heritage is evident and, in the second, tourism with an emphasis on heritage within the scope of Unesco. As a result, it was inferred that before the creation of the World Heritage Convention, there were already interests (notably economic) in using (world) heritage as a resource for tourism.